Light microscopic study on the absorptive cells and goblet cells in the intestine of adult common carp Cyprinus carpio: 1Khalid Hadi Kadhim, 2Abdulkarim J Karim and 2Khalid Kamil Kadhim - Kadhim, Khalid Hadi (The Iraqi Journal of Veterinary Medicine, 2019)
The purpose of this study was to describe of some histological structures and histochemical features of the absorptive cells and goblet cells in intestine of common carp. In this study, Fifteen adult male common carp were catching alive from the AL-Forat river, with age about (7 - 12) months and mean of their weight was (2100 ± 81 g) and mean standard length was (50.4 ± 3.1 cm), immediately after death.Incision was made through the midventral line of the fish just from cranial to the anus to expose the intestine, specimens of intestine were taken and washed with (0.9 %) normal saline solution. Ten samples were obtained from different regions of each portion of the intestine (anterior, middle and posterior), fixed by either 10% neutral buffered formalin or Bouin’s solution approximately 24 hours at room temperature and then treated by routine histological processing. The stains were used, Hematoxylin and Eosin, periodic acid Schiff, Alcian blue pH 2.5, and Combinated Alcian blue PH 2.5 plus periodic acid Schiff. The Mean number, height and width of mucosal folds were measured and counts of goblet cells in the mucosal folds of each portion of the intestine. The results showed that the intestinal epithelium is simple columnar, the enterocytes were tall columnar cells with brush border; goblet cells were ovoid, located between the enterocytes. The folds composed of the entire thickness of the mucosa, mean number, height and width of the mucosal folds were few in posterior portion of intestine compare with that in other portions. The anterior portion of the intestine has largest number of mucosal folds, while has less number of goblet cells compare to middle and posterior portions of the intestine. The epithelial cells stained red-purple by periodic acid Schiff stain with Alcian blue, the goblet cells were take positive reaction with periodic acid Schiff stain, and with Alcian blue plus periodic acid Schiff, while negative with only Alcian blue stain. Glycoprotein staining intensity varied from very weak to moderate, whereby the presence of neutral, acidic and sulphatedglycoconjugates. In conclusion, numbers of goblet cells were observed to be increased towards posterior portion of intestine required as lubricant for fecal expulsion, and reversed relation between number of the folds and goblet cells.